(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2013)
The freshwater fish, Cirrhinus mrigala, was exposed to lethal and sub-lethal concentrations of cypermethrin (5.13 μg/l and 1.026 μg/l) and the histopathological changes were observed in liver tissues. Compared to the structure of control fish, exposed tissues were initially exhibited disarray of liver lobes, mild degree of degeneration of cytoplasm, occasional blood clots, congregation of nuclei, cloudy swelling of hepatocytes, granulisation of cytoplasm, hypertrophic, pyknotic nuclei, atrophic, hepatocytic nuclei, focal necrosis, vacuolation, shrinkage of hepatocytes, granular degeneration, rupture of blood vessels, necrosis dissolution of laminar structure and cytoplasmic disintegration in hepatocytes. In the sub-lethal concentration of cypermethrin, tissues initially exhibited few changes like slight disarray of liver lobes, mild degree of degeneration of cytoplasm, occasional blood clots, congregation of nuclei and cloudy swelling of hepatocytes, granulisation of cytoplasm, hypertrophic and pyknotic nuclei on 1 and 7 days. But on 14 and 21 day, certain degree of reorganisation in the structure of liver cords was observed.